Praktik Sosial Women Crisis Center (WCC) Nurani Perempuan Membangun Kolaborasi dengan Stakeholder - Khairunnisa, Khairunnisa; Afrizal, Afrizal; Jendrius, Jendrius (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
The alarming violence against women (KBG) in Indonesia requires the role of civil society to prevent and overcome it. Women Crisis Center Nurani Perempuan is a civil society organization (NGO) that works specifically to protect women and children from various acts of gender-based violence in West Sumatra Province. However, NGOs as non-profit institutions have challenges in terms of limited resources. This requires NGOs to collaborate with multi-stakeholders so that the implementation of case handling can run effectively. Unfortunately, the efforts of NGOs in attracting the attention of stakeholders in order to collaborate are still poorly studied. Thus, the presence of this study aims to describe the social practices of Women's Conscience to build collaboration with stakeholders, through identifying the activities carried out and what habituses are owned by staff and volunteers of Women's Conscience which enables them to build collaboration with stakeholders in efforts to protect women victims of KBG in West Sumatra. This research uses Bourdieu's theory and qualitative research methods. The results of this research show that there are five areas that are the focus of Women's Conscience in seeking to build collaboration, namely the provincial government, city government, police, community domain and the realm of providing and servicing safe houses. Activities to build collaboration in this domain are generally carried out through advocacy activities by analyzing opportunities owned by stakeholders, conducting face-to-face meetings and participating in multistakeholder discussions, and fulfilling all series of administrative requirements in the realm of government. The habitus of staff and volunteers also affects stakeholder involvement, such as having a high volunteer spirit, upholding accountability and always being committed as friends of women who are victims of KBG in West Sumatra. Staff and volunteers utilize network capital, which enables Nurani Perempuan to collaborate with stakeholders in the protection of women victims of KBG in West Sumatra.